Mixed Impact Aerobic Gymnastics on Decreasing Body Fat Percentage of Sanggar Rina Padang Members - Reviona, Chindy Angelin; Syampurma, Hilmainur; Neldi, Hendri (Jurnal Guru Peneliti Professional, 2017)
The problem in this study is body fat, a very large amount of body fat reserves will cause difficulties for the body, one of which, can gain weight or obesity. This study aims to determine the Mixed Impact Aerobic exercise on decreasing body fat in members of the gymnastics studio Rina Padang. This type of quasi-experimental research. The population in this study were members of the Rina Padang studio, amounting to 15 people so that the entire population was sampled, with varying ages. Retrieval of data in this study by measuring the thickness of body fat during the pre test and post test. After doing the exercises, 21 meetings 3 times a week. From these data, it can be seen whether there is an effect of Mixed Impact Aerobic exercise on decreasing the percentage of body fat in members (samples) of the Rina Padang gym. Based on the results obtained from the initial test and the final test on the measurement of fat, data analysis using the T-test, it was found that the body fat value t count was 10.35, the value was greater than the value in the table t table 2.145. So it can be concluded that there is a significant effect of Mixed Impact Aerobic exercise on decreasing the percentage of body fat in members (samples) of Rina's gym in Padang.